2012
DOI: 10.1017/s0007114512003856
|View full text |Cite
|
Sign up to set email alerts
|

Extra-virgin olive oil consumption improves the capacity of HDL to mediate cholesterol efflux and increases ABCA1 and ABCG1 expression in human macrophages

Abstract: The present study was aimed to investigate the effect of 12 weeks of extra-virgin olive oil (EVOO) consumption on the capacity of HDL to promote cholesterol efflux (CE) and to determine which CE pathways are modulated by EVOO consumption. Whole HDL and HDL 2 /HDL 3 subclasses were isolated from the plasma of twenty-six healthy volunteers before and after 12 weeks of EVOO consumption (25 ml/d). EVOO consumption increased the capacity of serum and HDL to mediate CE from THP-1, J774 macrophages and Fu5AH cells by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
2
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(57 citation statements)
references
References 64 publications
4
47
2
4
Order By: Relevance
“…Different studies have shown a modulation of the expression of cholesterol metabolism-related genes, such as abca1, abcg1 and srb1, in macrophages responding to treatment with polyphenols quercetin, resveratrol and extra virgin olive oil, another source of polyphenols (Voloshyna et al 2013;Lee et al 2013;Helal et al 2013). However, in our study, of all the analysed genes that are involved in cholesterol homoeostasis, only lss was up-regulated in PBMCs in response to the administration of GSPE in the STD-GSPE animals.…”
Section: Discussioncontrasting
confidence: 71%
“…Different studies have shown a modulation of the expression of cholesterol metabolism-related genes, such as abca1, abcg1 and srb1, in macrophages responding to treatment with polyphenols quercetin, resveratrol and extra virgin olive oil, another source of polyphenols (Voloshyna et al 2013;Lee et al 2013;Helal et al 2013). However, in our study, of all the analysed genes that are involved in cholesterol homoeostasis, only lss was up-regulated in PBMCs in response to the administration of GSPE in the STD-GSPE animals.…”
Section: Discussioncontrasting
confidence: 71%
“…Regarding the study design, out of the 15 studies, two were randomized, double-blind, placebo-controlled, and parallel-groups trials [32, 42], two were randomized, double-blind, and controlled clinical trials [30, 35], one was a randomized and double-blind trial [39], one was a randomized, controlled, and parallel study [44], one was a randomized, double-blind, and controlled crossover feeding trial [31], one was a randomized and single-blind crossover trial [33], two were randomized and controlled crossover studies [34, 38], one was a randomized and intervention crossover trial [36], two were double-blind crossover studies [37, 43], and two were pre-post studies [40, 41]. …”
Section: Resultsmentioning
confidence: 99%
“…Four studies [30, 33, 36, 42] included subjects with hypercholesterolemia or moderate hypercholesterolemia; seven studies [3741, 43, 44] included subjects with normal lipid levels, one study [32] included subject with adherence to a vegetarian diet for at least one year, and two studies [34, 35] included healthy males and healthy volunteers.…”
Section: Resultsmentioning
confidence: 99%
“…Cholesterol efflux was assessed by incubating the radiolabeled J774-macrophages for 4 h at 37°C with 50 μL/mL of apolipoprotein B-depleted plasma (PEG-treated plasma from wild-type or PON1-Tg mice)]; J774 macrophages transfected with hPON1 or MPM with 50 μg/mL of ApoA-1. The supernatants and the adherent cells (macrophages) were separated and prepared for [ 3 H]-cholesterol quantification as previously described by Loued et al [21]. A liquid scintillation counter was used to determine [ 3 H]-cholesterol level (counts/min or cpm) in both the supernatant and in macrophages (lysates).…”
Section: Methodsmentioning
confidence: 99%